Kekerasan Seksual di Lingkungan Pesantren - Dede Cindy Aprilia; Abdul Mu'ti; Sururin Sururin (Journal on Education, 2022)
Cases that have been rife some time ago in Islamic boarding schools regarding sexual violence have become an introspection on Islamic educational institutions, that what is in Islamic boarding schools is not to be taken granted (not a guarantee) as if everything in Islamic boarding schools is fine. There are things that need to be examined and corrected if they are true. The purpose of this research is to analyze sexual violence in Islamic boarding schools. This research approach is descriptive research using a qualitative approach. The results of this study can be concluded that there are several factors that cause sexual violence both internally and externally. There is also an impact experienced by students, one of which is the psychological impact. There are preventive efforts towards sex education in order to prevent cases of sexual violence in Islamic boarding schools, both the efforts made by the pesantren and the government. The existence of cases of sexual violence in the pesantren environment will tarnish the good name of the pesantren, however, it is not the pesantren that are at fault but only certain elements who have tarnished the good name of the pesantren. Because in any institution no one wants to create criminal acts such as sexual violence.